2003
DOI: 10.1203/01.pdr.0000061541.94620.12
|View full text |Cite
|
Sign up to set email alerts
|

Circadian and Sleep Development in Preterm Infants Occurs Independently From the Influences of Environmental Lighting

Abstract: This study investigated the effect of intermediate nursery illumination on circadian rhythm and sleep development of preterm infants. Preterm infants were randomly assigned to one of two intermediate nursery rooms: a dimly lighted room, the dim (control) group, or a day-night lighted room, the cycled (intervention) group. Continuous rectal temperature and sleep were recorded at 36 wk postconceptional age (before discharge) and at 1 and 3 mo corrected age at home. Preterm infants are exposed to continuous low o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 25 publications
1
41
2
2
Order By: Relevance
“…Besides, Boo et al (2002) conducted their study on neonates, who received mechanical ventilation, while our sample included no mechanically ventilated neonates. According to Mirmiran et al (2003), hospitalized neonates experience great stress induced by stressors such as constant and chronic exposure to poor or strong lighting, maternal separation, deprivation from maternal cuddle and deep sleep, and reactivity to light and sounds. Therefore, they conducted a study in 2003 in order to test the following hypothesis, "Neonates' sleep pattern and circadian rhythm are developed independently from environmental lighting".…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, Boo et al (2002) conducted their study on neonates, who received mechanical ventilation, while our sample included no mechanically ventilated neonates. According to Mirmiran et al (2003), hospitalized neonates experience great stress induced by stressors such as constant and chronic exposure to poor or strong lighting, maternal separation, deprivation from maternal cuddle and deep sleep, and reactivity to light and sounds. Therefore, they conducted a study in 2003 in order to test the following hypothesis, "Neonates' sleep pattern and circadian rhythm are developed independently from environmental lighting".…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, Boo et al (2002) found that premature neonates' exposure to cyclical twelve-hour lighting or continuous darkness did not significantly affect their weight gain (3). The results of studies by Kennedy et al (1997) and Mirmiran et al (2003) also illustrated that environmental lighting had no significant effect on neonates' weight gain (2,11).…”
Section: Such a New Environment Is Essential For The Development Of Tmentioning
confidence: 98%
See 2 more Smart Citations
“…424 Although there is a progressive shift towards sleep-wake circadian rhythmicity with maturation, this may occur independently of the amount of ambient light exposure, suggesting circadian entrainment may occur based upon an endogenous, exposure-independent pacer mechanism. 423,424 Presently, it is clear that the newborn does not achieve an obvious circadian pattern until 3 to 4 months chronologic age, and that, prior to term birth, there is an in utero entrainment.…”
Section: To 32 Weeks Gestational Age and Beyondmentioning
confidence: 99%